2023
DOI: 10.1021/acsanm.3c02759
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Graphene Supported Sn–M (M = Fe, Co, Ni, Cu, Zn) Dual-Atom Catalysts for CO2 Hydrogenation to HCOOH

Fang Ma,
Xin Chen

Abstract: This work selects a series of transition metals (Fe, Co, Ni, Cu, and Zn) and Sn metal to construct a series of Sn−M dual-atom catalysts (SnMN 6 /G). Formation energy calculations are conducted to evaluate the stability of the studied catalyst. The calculated results demonstrate that SnMN 6 /G (M = Fe, Co, Ni, Cu, Zn) dual-atom catalysts exhibit high structural stability. From the calculated electrostatic potential and Fukui(−) index, it is determined that the Sn atom is the main reaction site for CO 2 hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…125 Ma and Chen theoretically studied a series of Sn–M DACs. 126 DFT study was used to set up models for five systems of Sn–M (M = Fe, Co, Ni, Cu, Zn) on N-doped graphene. SnMN 6 /G configuration was found stable for all five systems as demonstrated by formation energy analysis.…”
Section: Dacs In Eco2rrmentioning
confidence: 99%
“…125 Ma and Chen theoretically studied a series of Sn–M DACs. 126 DFT study was used to set up models for five systems of Sn–M (M = Fe, Co, Ni, Cu, Zn) on N-doped graphene. SnMN 6 /G configuration was found stable for all five systems as demonstrated by formation energy analysis.…”
Section: Dacs In Eco2rrmentioning
confidence: 99%
“…Single- and dual-atom catalysts (SACs and DACs) are emerging heterogeneous catalysts and have attracted widespread attention because of their high atom utilization, tunable coordination environments, and superior catalytic performance. Several experimental and theoretical studies reported that SACs and DACs embedded in nitrogen-doped graphene and other 2D supports provide excellent electrocatalytic performance for a diverse set of electrochemical reactions. , Recently, theoretical studies have been reported exploring the electrochemical performance of DACs for CORR and CO 2 RR to C 2+ products. , For example, a series of phthalocyanine-based DACs were investigated for the rapid CO electroreduction toward ethylene (C 2 H 4 ) enabled by high CO adsorption energy and low CO dimerization energy . Several DACs such as FeFe, RuRu, CoCo, IrIr, and IrCo were disclosed as the best candidates for converting CO to C 2 H 4 .…”
Section: Introductionmentioning
confidence: 99%